#### Question

Prove the following identities, where the angles involved are acute angles for which the expressions are defined.

`sqrt((1+sinA)/(1-sinA)) = secA + tanA`

#### Solution

L.H.S

`= sqrt((1+sinA)/(1-sinA))`

`= =sqrt(((1+sinA)(1+sinA))/((1-sinA)(1+sinA))`

`=(1+sinA)/(sqrt(1-sin^2A)) = (1+sinA)/sqrt(cos^2A)`

`=(1+sinA)/cosA = secA + tan A`

=R.H.S

Is there an error in this question or solution?

Solution Prove the Following Identities, Where the Angles Involved Are Acute Angles for Which the Expressions Are Defined. Concept: Trigonometric Identities.